Critical Analysis of Green Human Resource Management in Indian Industries: Exploring Green HRM practices and their impact on corporate social responsibility (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In today’s scenario Business sustainability is the core value of many fortune companies in the long run in order to maximize their opportunities and to minimize their negative impact in the economy. “Going Green” and environmentally conscious business is the ultimate target of many private as well as public sector enterprises. “Green way” of business is to integrate the green initiatives with people, process, and technology. Now a day, the go green policies are adopting in various environment management techniques. In India, the corporate world is going global it’s become essential to explore green practices in the business as well as in an environment. This study focuses on various green HRM practices followed in the organization. The paper largely focuses on the various green HRM practices and the relationship between corporate social responsibility and the green human resource management. And the study extended giving suggestions to the human resource department about initiatives to make the organization green and utilization from those values.